Development of methods for designing rational trusses - Janušaitis, Rolandas; Keras, Valerijus; Mockienė, Jūratė (Journal of Civil Engineering and Management, 2003)
Striving for rationality and long-term reliability is seen in different periods of building activities. Application of linear programming methods has enabled to formalise this striving and to elaborate the necessary mathematical models. But later theoretical and practical investigations have disclosed that not always, when optimising in respect of one criterion, it is possible to obtain solutions rational in other aspects, and this stimulated the application of multicriteria optimization methods. It is useful in this case to apply the ideas of the game theory, game problems solving methods already applied in other building design fields. When adapting methods of the game theory to popular needs for truss designing, a criteria set involving 11 alternatives has been selected. Attempts have been made to find rational truss variants by applying different methods (method of proximity to an ideal point, Wald’s and Hurwitz’s methods). It has been found when using the method of proximity to an ideal point for rational truss designing that a truss with a sloping brace network and pivoted knots supported by a column and composed of rectangular box shapes is more valuable than other trusses. According to Wald’s and Hurvitz’s methods, among popular spans of 24 m such a truss is the truss with a lowered bottom chord. First Published Online: 26 Jul 2012